Benefits and pitfalls of captive conservation genetic management: Evaluating diversity in scimitar-horned oryx to support reintroduction planning. (January 2020) - Ogden, Rob; Chuven, Justin; Gilbert, Tania; Hosking, Caroline; Gharbi, Karim; Craig, Mark; Al Dhaheri, Shaikha Salem; Senn, Helen
Graphical abstract: Highlights: Scimitar horned oryx reintroductions have been supported by a 10-year genetic study. Global captive populations display marked genetic structure and variable diversity. Result data is important for meta-population management and individual founder selection. The interpretation of captive population genetic structure requires extreme caution. Abstract: The reintroduction of the scimitar-horned oryx to Chad is a multi-disciplinary endeavour, planned and implemented over the past decade, utilizing a wide range of conservation science applications to maximise the chances of long-term population sustainability. The principle of incorporating genetic diversity information into founder selection for species reintroductions is widely recognized; however, in practice, a full assessment of available ex-situ genetic variation is rarely attempted prior to identifying individuals for release. In this study we present the results of over ten years of research analyzing and interpreting the genetic diversity present in the key source populations for the Chad scimitar-horned oryx reintroduction. Three empirical genetic datasets (mitochondrial DNA sequence, nuclear DNA microsatellite and SNP markers) comprising over 500 individuals sampled from public and private institutions were analysed, accompanied by simulation studies to address applied questions relating to management of the reintroduction. The results strongly demonstrate the importance of conservation genetic analysis in ensuring that founders represent the greatest breadth of evolutionary diversity available. The inclusion of both intensively and lightly managed collections allowed us to bridge the gap between studbook and group managed populations, enabling the inclusion of individuals from populations that lack historic data on their origins, but which may hold unique diversity of significant conservation value. Importantly, however, our study also reveals the potential risks of applying standard population genetic approaches to multiple captive populations, for which small founder sizes are likely to strongly bias results, with potentially serious consequences for the genetic management of conservation breeding programmes.